Citation distributions and research evaluations: The impossibility of formulating a universal indicator - Rodríguez-Navarro Alonso (Journal of Data and Information Science)
To analyze the diversity of citation distributions to publications in different research topics to investigate the accuracy of size-independent, rank-based indicators. The top percentile-based indicators are the most common indicators of this type, and the evaluations of Japan are the most evident misjudgments.